Cooking Up Change: Family Cookbooks as Markers of Shifting Kitchen Politics - Weiskopf-Ball, Emily (Cuizine, 2013)
Despite the recent academic attention community cookbooks have finally been granted, little has been said about compiled family cookbooks. Even works such as Janet Theophano's Eat My Words, Andrea Eidinger’s "Gefilte Fish and Roast Duck with Orange Slices": A Treasure for My Daughter and the Creation of a Jewish Cultural Orthodoxy in Postwar Montreal” and Marie Drews’ examination of In Memory's Kitchen, are about works by, and for, an entire community rather than for family. Furthermore, though gender critics have long documented the imbalance of food-related work in the home by showing that women have always been the primary food makers, one cannot deny that the makeup of modern families has changed and that men and children are becoming more active in the kitchen. Drawing on past and current literature to analyse a family cookbook I made and gave to my cousin for her wedding, this essay draws academic attention to family cookbooks and family food practices. While the cookbook I analyse is predominantly feminine, the many male and child voices included in this collection, voices that are usually excluded from such works, prove that, when given a chance, these often silenced groups can, and do, impact a family's food habits.